COMPARATIVE GENOMICS OF MYOCILIN PROTEIN - R. RAMANATHAN,; R. RAMASAMY,; S. KRISHNAN, (International Journal of Pharma and Bio Sciences, 2015)
Glaucoma is one of the leading diseases which causes irreversible visual impairment and blindness throughout the world. It constitutes clinically and genetically heterogenous group of optic neuropathies. Specific mutations in the myocilin gene cause primary open angle glaucoma with varying age-of-onset and degree of severity. Though the structure of the gene and protein have been elucidated still the role of mutant protein is not clearly understood. To study myocilin and glaucoma-associated myocilin mutants in higher animals and to understand, how these molecules may alter intraocularpressure and outflow resistance, it would be more helpful if we have animal models which could be used in the study. For finding out suitable animal models, sequence anlysis approach has been the first step in many diseases. Here we took a sequence analysis approach to know more about the related orthologes of myocilin proteins from different species.